2020
DOI: 10.1093/mnras/staa2982
|View full text |Cite
|
Sign up to set email alerts
|

The host galaxies of z = 7 quasars: predictions from the BlueTides simulation

Abstract: We examine the properties of the host galaxies of z = 7 quasars using the large volume, cosmological hydrodynamical simulation BlueTides. We find that the 10 most massive black holes and the 191 quasars in the simulation (with MUV, AGN < MUV, host) are hosted by massive galaxies with stellar masses log (M*/M⊙) = 10.8 ± 0.2, and 10.2 ± 0.4,which have large star formation rates, of $513\substack{+1225 \\-351}M_\odot /\rm {yr}$ and $191\substack{+288 \\-120}M_\odot /\rm {yr}$, respectively. The hosts of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 118 publications
11
51
0
Order By: Relevance
“…Several quasar host galaxies have been resolved in their [C II] emission on a few kpc scale at redshift ≈6. Even in this case, the dynamical mass estimates for the host galaxies give masses more than an order of magnitude below the values expected from the local scaling relation (Decarli et al, 2018), in agreement with the results for galaxies at z ≈ 7 derived from cosmological hydrodynamical simulations (Marshall et al, 2020).…”
Section: Evolution Of the M Bh -M Bulge Relationsupporting
confidence: 88%
“…Several quasar host galaxies have been resolved in their [C II] emission on a few kpc scale at redshift ≈6. Even in this case, the dynamical mass estimates for the host galaxies give masses more than an order of magnitude below the values expected from the local scaling relation (Decarli et al, 2018), in agreement with the results for galaxies at z ≈ 7 derived from cosmological hydrodynamical simulations (Marshall et al, 2020).…”
Section: Evolution Of the M Bh -M Bulge Relationsupporting
confidence: 88%
“…These studies revealed that z  6 optically luminous (M 1450  −26 mag) quasars have, on average, ∼10× more massive SMBHs than the local coevolution relations for a given velocity dispersion and/or dynamical mass of the host, suggesting that SMBHs were formed significantly earlier than their host galaxies. This result is in tension with hydrodynamic simulations of quasars (e.g., Hopkins et al 2006;Lupi et al 2019;Marshall et al 2020). However, our understanding of z  6 quasars has been biased to the most luminous (and presumably most massive) SMBH population (Lauer et al 2007;Volonteri & Stark 2011;Schulze & Wisotzki 2014).…”
Section: Introductionmentioning
confidence: 70%
“…A rotation curve that rises into the central (sub)kiloparsec regions of galaxies is frequently attributed to the existence of a massive galactic bulge (see Sofue 2016, for a review). Indeed, hydrodynamic simulations of z  7 quasars found that their host galaxies are typically bulge-dominant massive systems (Tenneti et al 2019;Marshall et al 2020). We fit the observed velocity profile V rot (r) with a simple spherical Plummer potential (Plummer 1911),…”
Section: Gas Dynamical Modelingmentioning
confidence: 99%
“…BPASS is extensively used for interpretation of massive star populations (e.g. Pahl et al 2021;Cullen et al 2021;Vijayan et al 2021;Neugent 2021;Marshall et al 2020;Stevance et al 2020b;Neugent et al 2020;Shivaei et al 2020;Topping et al 2020;Dorn-Wallenstein & Levesque 2020;Wilkins et al 2020;Chrimes et al 2020;Sanders et al 2020). Its accuracy and capabilities in the low mass regime have been explored through the white dwarf progenitor initial to final mass ratio (Eldridge et al 2017), the impact of low mass binary stars on understanding ages of globular clusters and elliptical galaxies (Stanway & Eldridge 2018) and consideration of the type Ia supernova rate (Tang et al 2020), producing good matches to the data in each case.…”
Section: Bpassmentioning
confidence: 99%